Review: Management Technology Transfer in the Indonesian Pharmaceutical Industry - Sumayyah, Shofiah; Resca Harda, Adila; Aliza Putriana, Norisca (Universitas Padjadjaran (Unpad), 2023)
Thisreviewarticlefocusesontechnologytransferinthepharmaceuticalindustry,specifically discussingits importance,guidelines, process, and documentation intheIndonesiancontext.Thepurposeis toprovideadetailedunderstandingoftechnologytransfer from drug discovery to product development, including the reasons for its utilizationanditssignificanceinthepharmaceuticalsector.Themethodologyemployedforthisreview involvedsearching onlineliterature throughplatformssuchasScienceDirectandGoogleScholarusingkeywordslike